Analisis Kualitas Laporan Keuangan Berdasarkan Kompetensi SDM dan Pemanfaatan Sistem Informasi Akuntansi pada Puskesmas 23 Ilir Kota Palembang - Fadiah Agmis; Yuliana Sari; Desi Indriasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to evaluate the quality of financial statements of the Regional Public Service Agency based on the ability of human resources and the utilization of accounting information systems at Puskesmas 23 Ilir Palembang City. Data collected through interviews, documentation, and observation are included in qualitative descriptive research. The financial field of Puskesmas 23 Ilir Palembang City became the data source. The triangulation method ensures data validity. Seven informants from the Finance Division of Puskesmas 23 Ilir Kota Palembang were involved in the interviews. The Budget Realization Report, Balance Sheet, Operational Report, Cash Flow Statement, Statement of Changes in Equity, and Notes to Financial Statements were examined, and observations were made to find out how the organization prepares financial statements. The interview results show that the ability of employees is continuously improved through training and technical guidance and accounting information systems, which support the suitability of the quality of financial statements.